Maternal and perinatal effects of pregnancy-induced hypertension. - Távara Orozco, Luis (2015)
From july 1988 to june 1992, 18 732 deliveries were atended in Obstetrics and Gynecology Department of María Auxiliadora Hospital. During this period 1309 women with preeclampsia and 146 women with eclampsia also were atended (incidence 7,0% and 0,8% respectively). Using a cohorte investigation model we found that PIH is an important risk factor to thirth trimester heamorrage, induced labor, cesarea section, postapartum heamorrage, puerperal infection and preterm delivery. Besides, we found among PIH patients most frecuency of low weigth newborn, asfixia, respiratory distress syndrome, ictericia and infection of newborn. Finally, PIH is clearly a very important risk factor to maternal mortality and perinatal mortality.